Microwave Energy as an Intensification Factor in the Heat-Mass Transfer and the Polyextract Formation - Burdo O.G.; Syrotyuk I.V.; Alhury U.; Levtrinska J.O. (Problems of the Regional Energetics)
The prospects of using the specifics of food raw materials structure for organizing mass transfer in the processes of extraction and dehydration has been shown. Authors studied in depth, in comparison with existing studies, selective effect of microwave energy on moisture in food raw materials. It has been shown that targeted energy supply to nanoscale elements in food raw materials is the basis for the creation of innovative technologies. The instrument for controlling such processes can be an electromagnetic field. A successful combination of the structure of food raw materials and field parameters can initiate a powerful flow of target components from product volume. Authors have analyzed driving forces of the effect of "barodiffusion". Mechanisms and stages of the processes of components transfer from plant raw materials were proposed for the gradientless supply of electromagnetic energy. The technique, stand and results of visualization of the effect of "barodiffusion" were presented. Created stand includes an electromagnetic energy generator equipped with a digitized endoscopic camera shielded from the field, which allowed the authors to get a visualization of the phenomenon for the first time. The results of experimental studies of extraction and evaporation processes in the microwave field during the processing of food systems of different structure were considered: alcohol-water-containing, dispersed and homogeneous. Obtained results testify to the prospects of introduction of equipment using the effect of "barodiffusion" in the technology of cognac spirits, oils, polyextracts, essences, food concentrates, phytopreparations.